MINIMAL INHIBITORY CONCENTRATION (MIC) TEST STRIP - GRYTA, Pawel; URBANIK-SYPNIEWSKA, Teresa; BILINSKA, Nina; TURSKA-SZEWCZUK, Anna; ROGALSKI, Jerzy; SZLACHETKA, Krzysztof; KOZIEL, Agnieszka; PALUSINSKA-SZYSZ, Marta; CHOMA, Adam; DWORACZEK, Katarzyna; KUTKOWSKA, Jolanta (2024)
The subject of the invention is a test strip for detecting the minimum inhibitory concentration (MIC), intended to be placed on a culture medium in a microbial culture vessel, and said test strip (1 ) is provided in the form of a layered composite having at least a support layer (2) and combined with the support layer (2) is the base layer (3), where both layers bonded together have the form of rectangular plates corresponding in shape and size, and a microbial growth inhibitor is applied to the surface of the support layer (2), the concentration gradient of which is planned along the longer side support layer (2), and the base layer (3) is equipped with a printed scale (4) indicating the concentration of the said growth inhibitor placed on the support layer, and according to the invention the support layer is made of a fibrous composite. L'objet de l'invention est une bandelette réactive pour détecter la concentration minimale inhibitrice (CMI), destinée à être placée sur un milieu de culture dans un récipient de culture microbienne, et ladite bandelette réactive (1) est fournie sous la forme d'un composite stratifié ayant au moins une couche de support (2), et combinée à la couche de support (2) est la couche de base (3), les deux couches liées ensemble ayant la forme de plaques rectangulaires correspondant en forme et taille, et un inhibiteur de croissance microbienne est appliqué à la surface de la couche de support (2), dont le gradient de concentration est planifié le long de la couche de support latérale plus longue (2), et la couche de support (3) est équipée d'une échelle imprimée (4) indiquant la concentration dudit inhibiteur de croissance placé sur la couche de support, et selon l'invention, la couche de support est constituée d'un composite fibreux.